2008
DOI: 10.1557/jmr.2008.0205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dynamic indentation on the mechanical response of materials

Abstract: Dynamic indentation techniques are often used to determine mechanical properties as a function of depth by continuously measuring the stiffness of a material. The dynamics are used by superimposing an oscillation on top of the monotonic loading. Of interest was how the oscillation affects the measured mechanical properties when compared to a quasi-static indent run at the same loading conditions as a dynamic. Single crystals of nickel and NaCl as well as a polycrystalline nickel sample and amorphous fused quar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 18 publications
1
24
0
2
Order By: Relevance
“…In this method the indentation is arrested and a small unload is carried out to determine the contact stiffness at a range of depths before reloading during the indentation experiment. It has been suggested that when CSM is used to measure the mechanical properties of metal specimens, there is an influence of strain rate that results in a difference in hardness values when compared with quasi-static nanoindentation [19]. However, it was explicitly stated that no effect is expected or was observed that influences the elastic properties measured using CSM.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In this method the indentation is arrested and a small unload is carried out to determine the contact stiffness at a range of depths before reloading during the indentation experiment. It has been suggested that when CSM is used to measure the mechanical properties of metal specimens, there is an influence of strain rate that results in a difference in hardness values when compared with quasi-static nanoindentation [19]. However, it was explicitly stated that no effect is expected or was observed that influences the elastic properties measured using CSM.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…However, two recent studies 50,51 have raised questions on the credibility of data obtained by the continuous stiffness measurement technique and underscore vital practical limitations particularly for soft materials such as polymers. For the bulk materials under investigation here, it can be assumed that the stiffness of the material is not a function of indentation depth and therefore a virtual unloading slope can be calculated from the stiffness as determined from the final unloading slope:…”
Section: 48mentioning
confidence: 99%
“…Strain gradient plasticity has been applied by several others to help understand microbend tests (Shi et al, 2008), plasticity (Abu-Al-Rub, 2008;Abu-Al-Rub and Voyiadjis, 2006;Qu et al, 2006;Volokh and Trapper, 2007;Wang et al, 2007), hardening effects (Abu-Al-Rub, 2008;Zhang et al, 2007), interface fracture and plasticity (Abu-Al-Rub, 2008;Siddiq et al, 2007) and the Taylor dislocation model (Hwang et al, 2004;Liu et al, 2005). The main concern is that the dissipative energy associated with even small oscillatory displacements of sharp tips could result in different properties (Cordill, 2007;Cordill et al, 2008), particularly with regard to dislocation nucleation and theoretical shear stress determinations. For example, at the macroscale, it has been known for some time that relatively small resonant-induced displacements on aircraft structures can lead to premature failure.…”
Section: Introductionmentioning
confidence: 99%